Enteric glial cell diversification is influenced by spatiotemporal factors and source of neural progenitors in mice - Lefèvre, Marie A.; Godefroid, Zoé; Soret, Rodolphe; Pilon, Nicolas (Frontiers in Neuroscience, 2024)
Previously focused primarily on enteric neurons, studies of the enteric nervous system (ENS) in both health and disease are now broadening to recognize the equally significant role played by enteric glial cells (EGCs). Commensurate to the vast array of gastrointestinal functions they influence, EGCs exhibit considerable diversity in terms of location, morphology, molecular profiles, and functional attributes. However, the mechanisms underlying this diversification of EGCs remain largely unexplored. To begin unraveling the mechanistic complexities of EGC diversity, the current study aimed to examine its spatiotemporal aspects in greater detail, and to assess whether the various sources of enteric neural progenitors contribute differentially to this diversity. Based on established topo-morphological criteria for categorizing EGCs into four main subtypes, our detailed immunofluorescence analyses first revealed that these subtypes emerge sequentially during early postnatal development, in a coordinated manner with the structural changes that occur in the ENS. When combined with genetic cell lineage tracing experiments, our analyses then uncovered a strongly biased contribution by Schwann cell-derived enteric neural progenitors to particular topo-morphological subtypes of EGCs. Taken together, these findings provide a robust foundation for further investigations into the molecular and cellular mechanisms governing EGC diversity.